2020
DOI: 10.1093/gji/ggaa021
|View full text |Cite
|
Sign up to set email alerts
|

Moho depth of the British Isles: a probabilistic perspective

Abstract: SUMMARY We present a new Moho depth model of the British Isles and surrounding areas from the most up-to-date compilation of Moho depth estimates obtained from refraction, reflection and receiver function data. We use a probabilistic, trans-dimensional and hierarchical approach for the surface reconstruction of Moho topography. This fully data-driven approach allows for adaptive parametrization, assessment of relative importance between different data-types and uncertainties quantification on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Estimates of the Curie isotherm at its shallowest in the study area place it at similar average depths of ca.30 km (Fichler et al., 2011; Kubala et al., 2003). Under the graben, Moho depth does become shallow, up to 22 km in places (Licciardi et al., 2020). Referring to Figure 8a, modelled heatflow is higher towards the graben centre, which suggests some correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the Curie isotherm at its shallowest in the study area place it at similar average depths of ca.30 km (Fichler et al., 2011; Kubala et al., 2003). Under the graben, Moho depth does become shallow, up to 22 km in places (Licciardi et al., 2020). Referring to Figure 8a, modelled heatflow is higher towards the graben centre, which suggests some correlation.…”
Section: Discussionmentioning
confidence: 99%
“…These hyperparameters are effectively treated as model parameters to be inferred from the input data by the rjMcMC sampling. They provide an estimate of the posterior uncertainties on data errors and simultaneously act as weighting factors of different data types (Bodin, Salmon, et al., 2012; Licciardi et al., 2020). This is of key importance in our joint inversion scheme, as the relative importance of each data type (VR, AFT, BHT, and porosity data) is usually not known a priori.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have shown the advantages of transdimensional inference (see Sambridge et al., 2013, for a review). Examples of successful applications of this type of algorithm can be found in seismology (Bodin, Sambridge, et al., 2012; Piana Agostinetti et al., 2015; Ravenna & Lebedev, 2017), mixture modeling in geochronology (Jasra et al., 2006), geospatial analysis (Bodin, Salmon, et al., 2012; Licciardi et al., 2020), exploration geophysics (Ray et al., 2016), stratigraphy (Charvin et al., 2009), magnetotellurics (Mandolesi et al., 2018; Xiang et al., 2018), geoacoustics (Dettmer et al., 2010; Dosso et al., 2014), and borehole geophysics (Reading & Gallagher, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the Curie isotherm at its shallowest in the study area place it at similar average depths of ca.30 km (Fichler et al, 2011;Kubala et al, 2003). Under the graben, Moho depth does become shallow, up to 22 km in places (Licciardi et al, 2020). Referring to Fig.…”
Section: Heat Flow Modelling -Impact and Implicationsmentioning
confidence: 97%